The Athenian Constitution - Aristotle, 385 BCE-323 BCE; Kenyon, Frederic G., Sir (Frederic George), 1863-1952 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Athenian Constitution" by Aristotle is a work written between 328-322 BC. Lost for centuries and rediscovered on Egyptian papyrus in the 1890s, it describes the political system of ancient Athens in unprecedented detail. The text traces the evolution of Athenian government through various constitutional forms and explains the city's institutions, including citizenship, magistrates, and courts. Its discovery transformed Greek historical study by revealing contemporary information found nowhere else in ancient literature. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Constitution_of_the_Athenians_(Aristotle)
Release date is 2008-07-21
Produced by Al Haines
Keywords: Classical literature; Constitutional history -- Greece -- Athens -- To 146 B.C.; Athens (Greece) -- Politics and government -- Early works to 1800